The interaction of intestinal bacteria and feed: a case study of intensive-duck husbandry in Central Java - Susanti, R.; Dafip, M.; Christijanti, W.; Yuniastuti, A. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This study was aimed to compare sugars and amino acid content in duck’s feed and the intestinal bacteria's effects to improve ducks' quality. This research was an observational exploration involving five duck husbandries from Semarang, Temanggung, Magelang, Pati, and Salatiga District, Central Java. A total of 5 g of intestinal contents were collected from each of the five ducks randomly selected from each husbandry. The feed and intestinal contents were then analyzed using high-performance liquid chromatography (HPLC). The highest amino acid types were glutamate, aspartate, lysine, valine, and isoleucine, while the lowest was asparagine found in all sample farms. Intestinal contents freshly extracted then placed in dark bottles sterile for microbiome analysis with primers 6S rRNA V3-V4 genome identification. The concentration of glucose, fructose, and galactose in the intestine has increased significantly caused by digested polysaccharides. The composition of bacteria plays a vital role in digesting polysaccharides, makes them quickly absorbed by duck’s intestine cells. The abundance of bacteria in all sample locations was dominated by the phylum Firmicutes, especially Lactobacilalles, Bacilalles, and Clostridialles. Over feeding may not effective in sugar and essential amino acid absorption, however, it may play an essential role in the diversity of gut bacteria to produce necessary component for duck’s physiology.